Cytochrome b5 shifts oxidation of the anticancer drug ellipticine by cytochromes P450 1A1 and 1A2 from its detoxication to activation, thereby modulating its pharmacological efficacy - Kotrbová, Věra; Mrázová, Barbora; Moserová, Michaela; Martínek, Václav; Hodek, Petr; Hudeček, Jiří; Frei, Eva; Stiborová, Marie (Biochemical pharmacology, 2011)
Ellipticine is a pro-drug, whose activation is dependent on its oxidation by cytochromes P450 (CYP) and peroxidases. Cytochrome b5 alters the ratio of ellipticine metabolites formed by isolated reconstituted CYP1A1 and 1A2, favoring formation of 12-hydroxy- and 13-hydroxyellipticine metabolites implicated in ellipticine-DNA adduct formation, at the expense of 9-hydroxy- and 7-hydroxyellipticine that are detoxication products. Cytochrome b5 enhances the production of 12-hydroxy and 13-hydroxyellipticine. The change in metabolite ratio results in an increased formation of covalent ellipticine-DNA adducts, one of the DNA-damaging mechanisms of ellipticine antitumor action. This finding explains previous apparent discrepancies found with isolated enzymes and in vivo, where CYP1A enzymatic activation correlated with ellipticine-DNA-adduct levels while isolated CYP1A1 or 1A2 in reconstituted systems were much less effective than CYP3A4. The effect of cytochrome b5 might be even more pronounced in vivo, since, as we show here, ellipticine increases levels of cytochrome b5 in rat liver. Our results demonstrate that both the native 3D structure of cytochrome b5 and the presence of the heme as an electron transfer agent in this protein enable a shift in ellipticine metabolites formed by CYP1A1/2.